The Effectiveness of Prenatal Yoga in Reducing Stress Among Pregnant Women: A Holistic Approach to Maternal Well-being - Marwati, Marwati (Trigin Institute, 2025)
Stress during pregnancy is a significant concern as it can negatively impact both maternal and fetal health, increasing the risk of complications such as preterm birth, low birth weight, and developmental issues. Prenatal yoga has been suggested as an effective non-pharmacological intervention to reduce stress, yet research on its comprehensive benefits remains limited. This study aims to evaluate the effectiveness of prenatal yoga in reducing stress levels among pregnant women and to explore its secondary benefits, including improved sleep quality, mood enhancement, and reduced pregnancy complications. A quasi-experimental study was conducted with a sample of pregnant women divided into an intervention group (prenatal yoga participants) and a control group (non-participants). The intervention group participated in structured prenatal yoga sessions three times per week for eight weeks. Stress levels were measured using the Perceived Stress Scale (PSS) before and after the intervention. Secondary outcomes such as sleep quality, mood stability, and pregnancy-related complications were also assessed through self-reports and medical evaluations. The findings indicate a significant reduction in stress levels among the prenatal yoga group compared to the control group (p < 0.05). Participants also reported improved sleep quality, better emotional regulation, and a lower incidence of pregnancy-related complications. These results suggest that prenatal yoga is an effective and holistic approach to stress management during pregnancy. Prenatal yoga is a safe, accessible, and beneficial practice for reducing stress in pregnant women. Given its positive impact on maternal well-being, healthcare providers should consider incorporating prenatal yoga into standard prenatal care programs. Future research with larger sample sizes and objective stress markers is recommended to further validate these findings.